CRITICAL REVIEW OF MEDHYA RASAYANA DRUGS MENTIONED IN AYURVEDA - TRADITIONAL INDIAN MEDICINE (International Journal of Ayurveda and Pharma Research, 2016)
Ayurvedic system of medicine has mentioned several medicinal preparations under the category 'Medhya'. By virtue of inducing mental upliftment as major influence several medicinal plants mentioned as 'Rasayana drugs' in Ayurveda are primarily claimed as 'Medhya'. Further there is a special class of Rasayana drugs called 'Medhya Rasayana' which is supposed to be having specific influence on brain functions. Cognitive deficits like memory disorders are found in high prevalence among the aged. In Ayurvedic literature, impairment of memory is mentioned as Smriti bhramsha which occurs due to vitiation of Rajo and Tamo doshas. It has been noted that cognitive functions are thoroughly affected due to stress and other related psychological disorders. It is clearly emphasized that Medha (intellect) and Buddhi (wisdom) deteriorate in these conditions. People's lifestyle also has an additional influence on the intellectual capacity. Several Medhya Rasayana drugs mentioned in Ayurveda have multi-dimensional actions having influence on memory. They not only enhance the intellectual capacity but also rejuvenate the whole system and their pathways.